Does visual attention impact on decision making in complex dynamic events? - Hüttermann, S.; Helsen, W. F.; Put, K.; Memmert, D. (Journal of Sport & Exercise Psychology, 2018)
In recent years, several publications examined the underlying mechanisms that might have an impact on decision-making processes under time pressure. This study investigated how individual differences in attentional capability relate to decision making in complex dynamic offside events. A total of 24 professional football assistant referees (ARs) performed an offside decision-making task and an attention-demanding task. ARs with higher attentional capability along the horizontal meridian of their attentional focus made fewer mistakes when judging offside situations in football than ARs with lower capability. This implies that being able to rely on high-attentional capabilities in situations requiring conscious perception of multiple processes is likely to be beneficial for the ultimate decision-making performance.